PEDAGOGICAL AND PSYCHOLOGICAL OPPORTUNITIES OF TEACHING A NATIONAL HANDICRAFT IN TECHNOLOGICAL EDUCATION ON THE BASIS OF A CREATIVE APPROACH (Scientific journal of the Fergana State University, 2023)
In this article, pedagogical and psychological possibilities for studying national handicrafts by students of secondary schools based on a creative approach have been developed. The use of visualization techniques, teaching,developing imagination in a problematic situations effectively help students have a high level of knowledge, receive and create the ground for them to grow into qualified professionals in the future.